DEVELOPMENT OF MULTIPLEX PCR BASED ASSAY FOR THE CONCURRENT DETECTION OF PATHOGENIC MICROORGANISMS - ALI, AQEEL MOHAMMED; S., VIMALA GANDHI; MALLA, SUDHAKAR (International Journal of Current Pharmaceutical Research, 2014)
Salmonella enterica is an important enteric pathogen which causes gastroenteritis and enteric fever in humans and is widely spread in nature. Outbreaks of Salmonella infections are frequently reported in both developed and developing countries, as this pathogen spreads very rapidly by means of water and the food chain. A multiplex PCR (mPCR) assay was developed for the detection of multiple Salmonella serotypes in different kind of food products. To increase specificity of this molecular method, three sets of oligonucleotide primer were used to detect the most prevalent salmonella species. Different primer pairs were used for the optimization of the multiplex PCR. The primer pair, ST FW and ST RV, was specific to Salmonella typhi and targeted a randomly selected sequence of 600bp. The primer pair SPFW and SPRV specific to Salmonella paratyphi for a sequence of 800bp in length. Likewise, the primers pairs SEFW and SERV were designed to amplify a sequence of about 1000bp from S. enterica. The Salmonella strains tested in this study were Salmonella typhi, Salmonella enterica and Salmonella Paratyphi. The STFW/STRV primer pair amplified 600bp DNA fragments when the DNA templates from Salmonella typhi, Salmonella enteritidis, Salmonella enterica and Salmonella paratyphi were tested. The DNA template of Salmonella paratyphi specifically amplified 800-bp fragments. Likewise, the DNA template for Salmonella enterica amplified 1000-bp fragment. This technique can be used routinely for the rapid detection of Salmonella spp. in food materials at low level of contamination with an enrichment time that depend in complexity of food product.